Effect of limb dominance and sex on neuromuscular activation patterns in athletes under 12 performing unanticipated side-cuts - Del Bel, M. J.; Fairfax, A. K.; Jones, M. L.; Steele, K.; Landry, S. C. (Journal of Electromyography and Kinesiology, 2017)
Non-contact ACL injuries are one of the most common injuries to the knee joint among adolescent/collegiate athletes, with sex and limb dominance being identified as risk factors. In children under 12 years of age (U12), these injuries occur less often and there is no sex-bias present. This study set out to explore if sex and/or limb dominance differences exist in neuromuscular activations in U12 athletes. Thirty-four U12 males and females had six bilateral muscles analyzed during unanticipated side-cuts. Principal component analysis was performed, capturing differences in overall magnitudes and timing of peak magnitudes. Two-way mixed-model ANOVAs determined significant limb effects with both sexes displaying (i) greater magnitudes in the lateral gastrocnemius and both hamstrings in the dominant limb and (ii) earlier timing of peak magnitudes in both gastrocnemii, both hamstrings and vastus medialis in the non-dominant limb, while no sex differences were identified. This study demonstrated that limb dominance, not sex, affects neuromuscular activation strategies in U12 athletes during unanticipated side-cuts. When developing injury prevention programs for younger athletes, an increased focus on balancing neuromuscular activations in both limbs could be beneficial in reducing the likelihood of ACL injuries in these athletes as they mature through puberty.